A PRELIMINARY STUDY OF FISHING CRAFTS AND GEARS OPERATING ALONG THE WAINGANGA RIVER OF MAHARASHTRA STATE, INDIA - WANJARI, RINKESH NEMICHAND; SHAH, TASADUQ HUSSAIN; TELVEKAR, PRASHANT; RAMTEKE, KARANKUMAR KISHORKUMAR; M, DHANALAKSHMI; RASHID, IFRAH (Journal of the Inland Fisheries Society of India, 2024)
The present study was carried out to examine various types of commonly used fishing crafts and gear operated by local fishermen in the Wainganga River in the Bhandara District of Maharashtra state. The survey was conducted monthly from June 2022 to May 2023. Three different types of fishing crafts and eleven types of fishing gear were observed during the present study, and the dimensions vary depending on the location along the river stretch. The fishing crafts were dug-out canoes, wooden-framed iron/tin/aluminium sheet boats, and plank-built boats. The fishing gears were gill net, cast net, dragnet, trap net, triangular push net, rod and line/hook and line, multiple head spears, and traps ('v'-shaped trap, cylindrical trap, long trap, box trap). The diversity of fish species in the river is threatened by a lack of awareness and the indiscriminate catching of fish with a small mesh-sized net. Therefore, promoting public awareness and providing relevant information regarding the usage of appropriate fishing gear with the proper mesh size may help to conserve the diversity of fisheries in the river and improve the livelihood of local fishermen.